KUALITAS PELAYANAN B US R APID T RANSIT (BRT) TRANS SEMARANG PADA KORIDOR I DAN II - KUKUH MIRSA; Puji Astuti; Ahmad Taufiq (Journal of Politic and Government Studies, 2016)
Increasing number of people who have a personal vehicle, but not matched by thedevelopment of an adequate road infrastructure, so that in large citiessuch as Semarang obviouscongestion that resulted in less effective and efficient in doing activities. In general, there are threedimensions that determines the mobility of public transport, namely the dimensions of evaluation ofservices, which will be determined by the user, the dimensions of service performance that is more interms of the owner (operator) public transport, and the dimensions of government policy (regulator ).This study suggests the quality of services Trans Semarang BRT corridor I andII, as both the corridoris a corridor crowded passenger of the other corridors.Methods of data analysis used in this research is to use a qualitative method with purposivesampling. In this research, data collection techniques used were observation or observation, interviewand documentation. The location of research is shelter in the corridors I and II.In this study covers two related, namely, the BRT Trans Semarang infrastructure and qualityof service on the corridor I and II. The discussion surrounding infrastructure on fleet size, condition ofthe fleet, the number of shelters and shelter conditions in the corridor I and II. Discussion on thequality of services includes about speed, convenience's security, and affordability of access to shelterandtravel expenses to be paid passengers.Conclusion The study shows First, the quality of service on the BRT Trans Semarang both interms of infrastructure as well as managing the BRT is good that the indicator can be seen from thenumber of fleets, accessto shelter, and concierge services. In addition, the number of passengers in thecorridor I and II increased. Second, On the condition of shelter BRT corridor I and II both in terms ofthe conditions of service and personnel, passengers give positive feedback. Only in rush hour full stopso that passengers crowded, so it needs the expansion of shelter in dense areas of passengers. As forequalization shelter in the corridor I and II has been uneven, which makes passenger access easier touse BRT. Keywords:Corridor, BRT Trans Semarang, Quality Service, Shelter.